2020
DOI: 10.1051/e3sconf/202021707016
|View full text |Cite
|
Sign up to set email alerts
|

Model of economic growth of the economy of small and medium-sized enterprises in the context of the spread of coronavirus infection

Abstract: In the last three months, the dynamics of economic development began to decline, due to the influence of the pandemic. The world was not ready for the big challenge of nature. The article describes the state of small and medium-sized businesses, the state of the economy, the market and the market environment of the countries most affected by the spread of the coronavirus, and also describes the support measures taken by the state for these enterprises. The article presents a model of economic growth for small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Using digital technology to keep small and medium-sized businesses running during the COVID-19 pandemic (Papadopoulos et al 2020). Government and state assistance will be required to aid economic recovery in the SME sector after the pandemic [33]. In China, during COVID-19, the government took some policies to support the SME sector, such as rent reduction, direct subsidies, Social Security deferral, credit guarantee, and loan support [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using digital technology to keep small and medium-sized businesses running during the COVID-19 pandemic (Papadopoulos et al 2020). Government and state assistance will be required to aid economic recovery in the SME sector after the pandemic [33]. In China, during COVID-19, the government took some policies to support the SME sector, such as rent reduction, direct subsidies, Social Security deferral, credit guarantee, and loan support [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tourist cancelled their planned tours in fear of Covid -19 to avoid infection of virus during travel time and gathering (Mamirkulova et al, 2020). Ukhanov et al, (2020) showed that dynamics of economic development began to decline, due to the pandemic and described the measure taken for enterprises for state, presented the model of economic growth for small and medium-sized enterprises. It was associated positively on impact of the development of the sanatorium and resort complex and infrastructure of recreation organizations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to (Ukhanov et al, 2020) the unperceived pandemic has not only meltdown the SMEs nations but equally cripple the growth of most economies. In this regards sustainability and resilient to pandemic is not only driven by the potential to produce a vaccine.…”
Section: Introductionmentioning
confidence: 99%